2016
DOI: 10.1111/ctr.12769
|View full text |Cite
|
Sign up to set email alerts
|

Routine ultrasonography surveillance of native kidneys for renal cell carcinoma in kidney transplant candidates

Abstract: Renal cell carcinoma (RCC) has a high incidence in the kidney transplant population and annual surveillance detects these tumors early in their natural history. Minimal guidelines exist regarding RCC surveillance in ESRD patients awaiting transplant. A retrospective review of our kidney transplant database examined the outcomes of annual ultrasonographic surveillance during initial kidney transplant evaluation and upon annual reassessment. Of 2642 patients listed for transplant, 145 patients were found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…It is well-established that the estimated rate of RCC development in native kidney is 10-to 100-times the incidence in the general, immunocompetent population (0.04%) (25,26), while RCC occurrence in the graft has been reported to be less frequent, accounting for approximately 10% of cases (5,27). Our series demonstrates one of the lowest incidences of RCC in native kidneys (0.5%) (11)(12)(13)(14)(15)(16)(28)(29)(30)(31)(32)(33)(34). Moreover, our results confirm those of a recent study and current literature findings, where the vast majority of renal malignancies were detected in the native kidneys of the recipients (85%) (33).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…It is well-established that the estimated rate of RCC development in native kidney is 10-to 100-times the incidence in the general, immunocompetent population (0.04%) (25,26), while RCC occurrence in the graft has been reported to be less frequent, accounting for approximately 10% of cases (5,27). Our series demonstrates one of the lowest incidences of RCC in native kidneys (0.5%) (11)(12)(13)(14)(15)(16)(28)(29)(30)(31)(32)(33)(34). Moreover, our results confirm those of a recent study and current literature findings, where the vast majority of renal malignancies were detected in the native kidneys of the recipients (85%) (33).…”
Section: Discussionmentioning
confidence: 47%
“…Cigarette smoking, hypertension, obesity and family history are also well-established risk factors for RCC. Male gender and African American race were also independently associated with RCC (31).…”
Section: Discussionmentioning
confidence: 93%
“…Despite having less advanced tumors at diagnosis, we showed that the OS in ESRD-RCC patients is significantly lower compared with RCC-only patients. In previous studies, ESRD-RCC patients showed a more favorable cancer-specific survival, compared with RCC patients only [8][9][10][11]28]. From a patient perspective, cancer specific survival only is less relevant for the ESRD-RCC patients since it does not capture the decreased survival due to ESRD.…”
Section: Discussionmentioning
confidence: 93%
“…УЗИ чаще всего применяется первым в диагностическом алгоритме постановки диагноза [29,30]. Если раньше перед специалистами УЗИ ставились минимальные задачи выявления опухоли, то сегодня с усовершенствованием ультразвуковой техники появились возможности уточняющей диагностики.…”
Section: Use Of the Contrast Agent In The Ultrasound Diagnosis Of Kidunclassified